2017
DOI: 10.1039/c6gc03558b
|View full text |Cite
|
Sign up to set email alerts
|

Organic sponge photocatalysis

Abstract: A polydimethylsiloxane organic sponge photocatalyst: high efficiency and reusability for visible light mediated cross-dehydrogenative coupling reactions. Through an easy-to-build continuous flow reactor, the sponge photocatalytic reaction can be facilely scaled up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 73 publications
0
55
0
Order By: Relevance
“…This attribute can lead to highly cross‐linked network after being fully cured within the same temperature ranges as typical CSPs; overtly introducing the possibility of a cold sintering mediated in situ polymer cross‐linking process. Polydimethylsiloxane (PDMS) is one such thermosetting polymer of industrial relevance, being widely employed in electronics, biomedical, cosmetic, food and also known for its good moldability, cost‐effectiveness, chemical, and mechanical robustness …”
Section: Introductionmentioning
confidence: 99%
“…This attribute can lead to highly cross‐linked network after being fully cured within the same temperature ranges as typical CSPs; overtly introducing the possibility of a cold sintering mediated in situ polymer cross‐linking process. Polydimethylsiloxane (PDMS) is one such thermosetting polymer of industrial relevance, being widely employed in electronics, biomedical, cosmetic, food and also known for its good moldability, cost‐effectiveness, chemical, and mechanical robustness …”
Section: Introductionmentioning
confidence: 99%
“…Owing to their unique mechanical, chemical and physical properties, in our recent studies, PDMS sponges were severed as 3D elastic skeletons for the high-performance of 3D stretchable and compressible conductors, [31] all-soft conductors, [32] oil/water separation interfaces, [33] and organic sponge photocatalyst. [34] In this study, PDMS sponges provide microchannel networks for the fast and efficient liquid transportation. "Dip-coat-dry" modification of the PDMS sponge surface using polyvinyl alcohol (PVA) was carried out to attain long-term hydrophilicity for water wicking by capillary action.…”
Section: Elastic Spongesmentioning
confidence: 99%
“…Despite these elegantp ioneering studies, conventionalf iltration or centrifugation is still required to recycle these kinds of gold catalysts, as they generally take the form of nanosized solid particles. [9b] Ta king into consideration the remarkable catalytic activity of gold nanoparticles together with the hydrophobicity of PDMS sponge,w hich should be beneficial for organic reactions in water,w er easonedt hat PDMS sponge-supported gold nanoparticles should be apromising heterogeneouscatalyst for efficient organic transformations in water.W ith our continued interest in PDMS sponge-supportedc atalysts [9] and nanometal catalysts, [10] in this paper,w ed emonstrate for the first time that ah ydrophobic PDMS sponge-supported nanometer gold can act as ah ighly efficient recyclable catalyst for cross-dehydrogenative coupling (CDC) [11] of tertiary amines with various nucleophiles in water.W eh ave found that PDMS sponge-supported nanogold can provide much better catalytic activity than free nanogold in water,i ndicating that this porous hydrophobic PDMS sponge material is ap romisings upport for highly efficient recyclable catalysts in water. [6] As water is widely seen as the greenest and cheapest reaction medium, [7] the development of green,h ighly efficient, and reusablec atalysts in water is highly anticipated.…”
mentioning
confidence: 96%
“…[2] In this regard,severalt ypes of gold(0) materials, such as gold nanoparticles (AuNPs), [3] nanoporous gold (AuNPore), [4] and gold nanoclusters, [5] have been well developed as catalysts for various organic transformations. [9] In addition to its convenient separation and purification, owing to the sponge-type morphology,t his catalyst exhibited high activity in water. These extra separation processes greatly limit their reusability and practical application in industry.T he recovery andr euse of catalystsi sa very important and longstanding challenge in green chemical synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation